Estrategias y toma de decisiones para la Educación a Distancia - Ligia María Angulo-Hernández (Universidad Nacional, Costa Rica, 2006)
An excellent process for distance education consists of many stages of design, development, evaluation, and revision. The design has to take into account, not only, themes, needs, students' characteristics, instruction; but also, technological commitment. This article explains some strategies and possible technological resources that can be used in the distance educational process. This article recommends to the Universities and Educational Institutions to give priority to these concepts in order to offer high-quality education.